Perspektif Hukum Teknologi Informasi dan Ham pada Fenomena Buzzer Politik di Media Sosial - Ni Komang Githa Chandra Dew; Komang Febrinayanti Dantes; Ni Ketut Sari Adnyani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aimsmto examineiin depthvthe perspective of information technology law and human rights on the phenomenon of political buzzers on social media within the context of digital development in the era of globalization. This research is motivated by the rapid advancement of information technology, which has brought significant changes in various aspects of society, including the political sphere that increasingly utilizes social media as a means of communication and information dissemination. The phenomenon of political buzzers has become a controversial issue, particularly during election periods, as it is often associated with the spread of inaccurate information, defamation, hate speech, and the manipulation of public opinion that may harm society and disrupt social stability. This study employs a normative legal research method using statutory and conceptual approaches. The results indicate that political buzzers generally operate under the justification of freedom of expression as part of human rights. However, such freedom is not absolute and must be limited to prevent violations of others' rights and to maintain public order. In this regard, information technology law in Indonesia, particularly through regulations governing digital activities, plays an important role in controlling deviant buzzer practices. Nevertheless, the absence of specific regulations explicitly governing political buzzers has resulted in less optimal law enforcement. Therefore, strengthening regulations and increasing public awareness in the wise use of social media are necessary to create a healthy, responsible, and sustainable digital ecosystem.